An Australian Approach to Space Warfare. Issue 2 (2nd September 2022) - Dowse, Andrew; Blake, Duncan; O'Sullivan, Emmet
ABSTRACT: Australia is currently experiencing a reinvigorated space program with a new space agency, significant industry investment in space ventures, and the Australian Defence Force embracing the military advantage conferred by space systems. Coincidentally, geostrategic instability has led Australia's government to raise its military preparedness in the face of increased risk of state-on-state conflict. Accordingly, military planners are considering not only what future space capabilities are needed by Australia, but the prospect of space warfare and what the state should do to protect its equities in the space domain. We conclude that developing a stronger normative framework is the best option for the preservation and growth of Australia's future space capabilities.